Analisis Pengaruh Marketing Mix Terhadap Kepuasan Konsumen Sepeda Motor - Wahyudi, Tri; Prawatya, Yopa Eka (ELKHA : Jurnal Teknik Elektro, 2012)
Abstract Marketing Mix is a tool for marketers who are composed of various elements of a marketing program that should be considered that the implementation of the marketing strategy to be successful. From research it appears that the variable Product, Price, Promotion, and Customer Service is the most significant variable affecting customer satisfaction variable Keywords Marketing Mix, Customer Satisfaction